Disturbance Observer Based on Fixed Time Sliding Mode Control and Optimal State Observer for Three-Phase Three-Level T-Type Inverters - Anh Tuan Duong; Thanh Long Pham; Van Nam Giap; Phuong Vu (IEEE Access)
This paper presents the advanced control method together with the disturbance rejection method with the aims to obtain the low of total harmonic distortion (THD). The expectation of the paper is that the output voltage is satisfied the requirements of the EN 62040 with the THD is less than 5%. Therefore, this paper proposes a new disturbance observer (DOB) without the requirement of the information of the first derivative disturbance for the three phase three level (TPTL) T-type inverter system. The proposed DOB is based on the information of the measurable states, which are used such an inversed model of T-type inverter to find the information of real disturbance. First, the DOB was designed based on the given measured and estimated states. However, to design the DOB, the state observer is required. Therefore, second, the state observer (SOB) was designed based on linear matrix inequality (LMI) to identify the optimal poles of the state-tracking error function. Third, the estimated states were used to construct the fixed time (FT) sliding mode control (SMC) to control the T-type inverter system. Fourth, the Lyapunov condition was used to verify the correction of the proposed method. The performance of the proposed control strategy is validated by simulations and experiments during steady-state, transients caused by load change, and unbalanced grid conditions. The estimated states precisely tracked the measured states. The output signals precisely converged to the predefined trajectories in a predefined time and the tracking errors are small. The obtained results showed that the proposed control method provided excellent steady-state and good performances with low THD in the line currents, zero steady-state error in the output voltage, and a very fast dynamic response.